Middlemarch - Eliot, George, 1819-1880 (First Avenue Classics, 2017)
Middlemarch's society is a complex web, and those who do not learn to navigate the intricate threads soon find themselves hopelessly entangled. In 1830s England, social status is no longer determined solely by birth, but by one's education, professional success, and choice of marriage partner. The inhabitants of Middlemarch must learn to reconcile their desires with society's expectations-or face the consequences. English author Mary Ann Evans used a male pseudonym-George Eliot-for her writing in an effort to combat the pervasive stereotypes that relegated female writers to frivolous, romantic subjects. Her novel challenged convention both in its unapologetic examination of political themes and in its scrutiny of daily life among the provincial middle class. First published in eight parts between 1871 and 1872, this is an unabridged version of Eliot's historical epic.